Fashions in Prayer Exhibit the Mysterious Love of Prophet Muhammad (SAW) to Allah (SWT) - Mohammad Abul Hossain (Universitas Ahmad Dahlan, 2020)
This study presents a structural view of the mysterious love of Prophet Muhammad (Sallallahu Alaihe Wasallam: SAW) to Allah (Subhanahu-Wa-Ta’ala: SWT) through the body fashions in prayer (Salah). The fashions in the unit of prayer (one Rak’ah Salah) are the sequence of (1) stand upright facing the direction of Al-Ka'bah, (2) bow down (Ruku), (3) stand up and (4) prostration (Sujood). In this study, the fashions in prayer were analyzed from the structural view point of human body. These observations have shown that the four fashions of body in a one unit (rak’ah) prayer represent the structure of four Arabic letters: (1) Alif ( ), (2) Lam ( ), (3) Lam ( ) and (4) Ha ( ). Consequent arrangement of these four letters leading the structure of Arabic word Allah ( ) which means the performing of one rak’ah salah, providing the internal written of the name of Allah ( ). Thus the Muslims become close to Allah (SWT) by performing prayer. Again, the recent development in medical science has shown that the skeleton structure of human body represents the structure of the Arabic word Muhammad ( ) (SAW) (American Journal of Medical Science and Medicine, Vol. 6, No. 1, page 1-4, January 2018). Therefore, as a whole, the fashions in prayer represent the internal written of the name of Allah ( ) (SWT) through the name of prophet Muhammad (SAW) as the structure of human body. These body fashions in prayer, practiced by Prophet Muhammad (SAW), exhibited the greatest love of Prophet Muhammad (SAW) to Allah (SWT).